2013
DOI: 10.1158/1541-7786.mcr-12-0632
|View full text |Cite|
|
Sign up to set email alerts
|

Balanced Tiam1-Rac1 and RhoA Drives Proliferation and Invasion of Pancreatic Cancer Cells

Abstract: Tiam1 is a rac1-specific guanine nucleotide exchange factor, and Tiam1-rac1 is involved in a number of cellular processes. Rac1 and RhoA act as molecular switches that cycle between GTP-and GDP-bound states to balance the activities of rac1 and RhoA. The downregulation of rac1 activity leads to upregulation of RhoA activity, which promotes invasion and migration of pancreatic cancers cells. At present, however, the role of Tiam1-rac1 and RhoA in pancreatic cancers is not fully understood. We found that Tiam1 w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 36 publications
3
32
0
1
Order By: Relevance
“…Silencing of Tiam1 or Par3 did not affect expression of one another, or Par6, or aPKC, but did disturb Par3-Tiam1 interaction, thus disturbing tight junction assembly. We found Tiam1 to play an important role in pancreatic cancer [23].…”
Section: Discussionmentioning
confidence: 69%
“…Silencing of Tiam1 or Par3 did not affect expression of one another, or Par6, or aPKC, but did disturb Par3-Tiam1 interaction, thus disturbing tight junction assembly. We found Tiam1 to play an important role in pancreatic cancer [23].…”
Section: Discussionmentioning
confidence: 69%
“…[36][37][38][39] A recent report suggests that a balance of Tiam1-Rac1-and RhoA-mediated signals is important for pancreatic cancer cell proliferation and invasion, respectively. 40 Knocking down Tiam1 in the tumor cells increased their migratory capacity, accompanied by increased RhoA activity. 40 Because Tiam1/ Rac signals have previously been considered imperative for lamellipodium formation, chemokine-induced motility, and homing of multiple other nontransformed cell types, 41 this observation points to a differential usage of Tiam1/Rac in cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…The inhibition of cell proliferation could be the consequence of, a) angiogenesis inhibition because angiogenesis is absolutely required for tumor growth; b) consequence of the inhibition of Rac1 which is also involved in cell proliferation (43) or c) a consequence of ZA treatment, we previously showed that ZA not only has anti-angiogenic activity but also anti-proliferative and pro-apoptotic effects (19). In this study, we observed that ZA induces apoptosis in OVCAR-5 in vivo model (Supplementary Fig S1A) and in HeyA8-MDR both in vitro and in vivo (Supplementary Fig S1B–D).…”
Section: Discussionmentioning
confidence: 99%